Qualitative analysis of the investment decision risk - Feshchenko, Olena; Yakimova, Yuliya (My University, 2018)
The article reveals the content of the concept of investment decisions, complexity of its adoption and implementation in conditions of uncertainty. Characteristic features are identified and key investment risk factors are described. A group of qualitative methods for quality analysis of the investment decision risk is studied in detail, and finally, the pros and cons of their use are revealed. У статті розкривається зміст поняття інвестиційного рішення, складність його прийняття та реалізації в умовах невизначеності. Визначено характерні ознаки та описано ключові фактори інвестиційного ризику. Детально досліджено групу якісних методів аналізу ризику інвестиційного рішення, а також виявлено переваги та недоліки їх використання.
Keywords: risk analysis; аналіз ризиків; інвестиційні рішення; investment decision